Preparation of highly water dispersible functional graphene/silver nanocomposite for the detection of melamine - Kumar, S. Vijay; Huang, Nay Ming; Lim, Hong Ngee; Zainy, Mazlinda; Harrison, Ian; Chia, Chin Hua (Elsevier, 2013)
A stable aqueous suspension of a functional graphene/silver (FG/Ag) nanocomposite was prepared by an environmentally friendly hydrothermal method. The precursor, functional graphene oxide (FGO), was prepared by covalent functionalisation of graphene oxide (GO) with a hydrophilic organosilane, N-(trimethoxysilylpropyl) ethylenediaminetriacetic acid trisodium salt (TETA). The attachment of functional groups on the GO surface maintained the aqueous stability of the FG/Ag nanocomposite even after the hydrothermal reduction. Field emission scanning electron microscopy (FESEM) images illustrated a uniform distribution of Ag nanoparticles on the FG surface. The surface enhanced Raman spectroscopy (SERS) activity of the nanocomposite was investigated using p-aminothiophenol (p-ATP) and melamine which can be detected as low as 2 × 10−8 and 2 × 10−7 M, respectively. The impressive water stability and the high SERS sensitivity of the FG/Ag nanocomposite make it a suitable substrate for trace analysis of a variety of drugs, additives or organic contaminants in water. The nanocomposite also showed a positive inhibition effect against the growth of Escherichia coli bacteria, eliminating the possibility of bacterial contamination of the sensor, thus prolonging the shelf-life of the sensing device.